Immuno-SPECT imaging of aberrant p53 expression in pancreatic ductal adenocarcinoma - Alakonya, H (2023)
Pancreatic ductal adenocarcinoma (PDAC) is a notoriously ferocious malignancy arising from the head of the pancreas, with aggressive biology and early-onset metastases. PDAC develop and progress asymptomatically with over 80% of the patients presenting for diagnosis with inoperable metastatic tumours that are resistant to standard therapies. Late diagnosis has resulted a grim increase of the five-year survival statistics from less than 5% to 8% over the past four decades.